Wear-out Failure Analysis of the Stainless Steel Hinge Joint in the Chain of Bucket Coal Elevator - Zhu Guoren; Liao Qingsong; Ren Fujian; Wen Zhengqi (Jixie chuandong)
According to the observation and analysis of the hinge joint（ friction pair） among pin,sleeve and roller in the chain of bucket coal elevator by means of scanning electron microscope,it shows that the wear mechanism of pin and sleeve is mainly abrasive wear accompany with fatigue wear after choosing the martensitic stainless steel material to produce parts. When the material of rollers is medium carbon alloy steel,the wear mechanism is corrosion wear and fatigue wear due to the effect of environmental medium,which is different from the dual sleeve.